If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-4X+X=6-7
We move all terms to the left:
X-4X+X-(6-7)=0
We add all the numbers together, and all the variables
X-4X+X-(-1)=0
We add all the numbers together, and all the variables
-2X+1=0
We move all terms containing X to the left, all other terms to the right
-2X=-1
X=-1/-2
X=1/2
| 134+24+3x+4=180 | | 47=(4y-3)+(3y+1) | | (3x+2)=1+x | | 3x-5(x+1)=37 | | x+22=2-13 | | 3x-300=154 | | 4b+17=5b | | -4x+8=2x+1+10 | | z+38=20z | | 67=8g | | 7b+10=b+46 | | 4c+21=7c | | 19+x=37+18 | | 8b-18=b+31 | | 8s-11=7s | | 2b-20=b | | X-2=0.8x+18 | | 18t+9=9* | | 11=9-2c | | 4a+8=a+50 | | 5w=9w-48 | | y^2-13y+42=y-6 | | 2(i+1=18 | | -6n=11/12 | | -2y+y=+3y+5y | | 4x+-20=8 | | 372/x=2/3 | | 149=243-v | | 280=-v+174 | | 208=-v+174 | | 5x=236 | | -w+209=86 |